2019
DOI: 10.1038/s41598-019-48587-2
|View full text |Cite
|
Sign up to set email alerts
|

An anti-inflammatory phenotype in visceral adipose tissue of old lean mice, augmented by exercise

Abstract: Visceral adipose tissue is an immunogenic tissue, which turns detrimental during obesity by activation of proinflammatory macrophages. During aging, chronic inflammation increases proportional to visceral adipose tissue (VAT) mass and associates with escalating morbidity and mortality. Here, we utilize a mouse model to investigate the inflammatory status of visceral adipose tissue in lean aging mice and assess the effects of exercise training interventions. We randomized adult (11 months; n = 21) and old (23 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 53 publications
2
27
0
2
Order By: Relevance
“…Therefore, we could expect from our ndings that the exercise program had a role in the decrease of NLRP3 in ammasome activation through ASC down-regulation, MCP-1, and MIP-1β; thus, improving the anti-in ammatory pro le through the IL-10 cytokine. Moreover, visceral adipose tissue surrounding the internal organs has in ammatory activity since it is associated with a greater number of pro-in ammatory cells in the tissue [31]. Therefore, the decreased levels of MCP-1, MIP-1β and IL-8 cytokines in our study also may be in part due to the abdominal fat loss, since these results showed a positive correlation between them (p<0.05).…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, we could expect from our ndings that the exercise program had a role in the decrease of NLRP3 in ammasome activation through ASC down-regulation, MCP-1, and MIP-1β; thus, improving the anti-in ammatory pro le through the IL-10 cytokine. Moreover, visceral adipose tissue surrounding the internal organs has in ammatory activity since it is associated with a greater number of pro-in ammatory cells in the tissue [31]. Therefore, the decreased levels of MCP-1, MIP-1β and IL-8 cytokines in our study also may be in part due to the abdominal fat loss, since these results showed a positive correlation between them (p<0.05).…”
Section: Discussionmentioning
confidence: 51%
“…Within BAT, treadmill training for 1 week was shown to increase PGC-1α [81,109], while voluntary wheel running for 11 days to 3 weeks and prolonged treadmill training (8 weeks) yielded no changes or decreases in PGC-1α [21,22,95,99,101]. Within WAT, PGC-1α seems to be more potently activated by exercise in both humans [116,117] and rodents [8,22,62,[99][100][101][111][112][113][114][115]. Swimming both acutely (2 h) and chronically (8 weeks) increased PGC-1α in subcutaneous WAT and epididymal WAT, with inconsistent increases or no change in inguinal WAT and visceral WAT [8,62,101,111,181].…”
Section: Dissimilarities Between Cold Exposure and Exercisementioning
confidence: 95%
“…In rodents, acute [8,62] and chronic exercise from 1-3 weeks [99][100][101]111] increased PGC-1α mRNA. Likewise, 8-10 weeks of protocols involving running (treadmill, voluntary wheel running, endurance training) and resistance training [22,[112][113][114][115] increased PGC-1α. In humans, PGC-1α mRNA increased in subcutaneous and omental WAT in response to 4-6 weeks of aerobic training [116,117].…”
Section: Activation Of Pgc-1αmentioning
confidence: 97%
See 2 more Smart Citations